Regional high iron deposition on quantitative susceptibility mapping correlates with cognitive decline in type 2 diabetes mellitus - Hu, Rui; Gao, Bingbing; Tian, Shiyun; Liu, Yangyingqiu; Jiang, Yuhan; Li, Wanyao; Li, Yuan; Song, Qingwei; Wang, Weiwei; Miao, Yanwei (Frontiers in Neuroscience, 2023)
Objective: To quantitatively evaluate the iron deposition and volume changes in deep gray nuclei according to threshold-method of quantitative susceptibility mapping (QSM) acquired by strategically acquired gradient echo (STAGE) sequence, and to analyze the correlation between the magnetic susceptibility values (MSV) and cognitive scores in type 2 diabetes mellitus (T2DM) Patients. Methods: Twenty-nine patients with T2DM and twenty-four healthy controls (HC) matched by age and gender were recruited in this prospective study. QSM images were used to evaluate whole-structural volumes (Vwh), regional magnetic susceptibility values (MSVRII) and volumes (VRII) in high-iron regions in nine gray nuclei. All QSM data were compared between groups. Receiver operating characteristic (ROC) analysis was used to assess the discriminating ability between groups. The predictive model from single and combined QSM parameters was also established using Logistic regression analysis. The correlation between MSVRII and cognitive scores was further analyzed. Multiple comparisons of all statistical values were corrected by false discovery rate (FDR). Results: Compared with HC group, the MSVRII of all gray matter nuclei in T2DM were increased by 5.1%-14.8%, with significant differences found in bilateral head of caudate nucleus (HCN), right putamen (PUT), right globus pallidus (GP) and left dentate nucleus (DN). The Vwh of most gray nucleus in T2DM group were decreased by 1.5%-16.9% except bilateral subthalamic nucleus (STN). Significant differences were found in bilateral HCN, bilateral red nucleus (RN), and bilateral substantia nigra (SN). VRII was increased in bilateral GP, bilateral PUT. VRII/Vwh was also increased in bilateral GP, bilateral PUT, bilateral substantia nigra (SN), left HCN and right STN. Compared with the single QSM parameter, the combined parameter showed the largest AUC of 0.86, with a sensitivity of 87.5% and specificity of 75.9%. The MSVRII in the right GP was strongly associated with List A Long-Delay Free Recall (List A LDFR) scores (r = -0.590, P = 0.009). Conclusion：In T2DM patients, excessive and heterogeneous iron deposition as well as volume loss occurs in deep gray nuclei. The MSV in high iron regions can better evaluate the distribution of iron, which is related to the decline of cognitive function.